The Effectiveness of an Inclusive Differentiated Learning Model Based on Local Wisdom on Learning Outcomes and Student Engagement in Elementary Schools - Machful Indrakurniawan; Ida Rindaningsih; Ria Wulandari (Journal of Educational Studies, 2026)
The persistent use of homogenized teaching approaches in diverse elementary classrooms often fails to accommodate students' varying learning readiness, interests, and abilities, resulting in suboptimal learning outcomes and low student engagement. To address this issue, this study aimed to examine the effectiveness of an inclusive differentiated learning model based on local wisdom, integrating Sidoarjo local cultural values and community-based learning contexts into classroom instruction to create more meaningful and inclusive learning experiences. The study employed a quantitative approach using a quasi-experimental non-equivalent control group design. The participants consisted of 49 fourth-grade students, including 25 students in the experimental class and 24 students in the control class. Data were collected through learning achievement tests and a student engagement questionnaire and analyzed using the Shapiro–Wilk normality test, Levene's homogeneity test, independent-samples t-test, and N-Gain analysis. The results revealed a statistically significant difference between the two groups (p < 0.001). The experimental class achieved a higher mean post-test score (85.76) than the control class (74.42), with an average difference of 11.34 points. Furthermore, the experimental class obtained a high N-Gain score (0.71), whereas the control class achieved a moderate N-Gain score (0.34). Student engagement in the experimental class was also consistently higher across all indicators, including active participation, interaction, enthusiasm, and teamwork. These findings demonstrate that integrating differentiated instruction, inclusive learning principles, and local wisdom effectively enhances both students' academic achievement and engagement. The study contributes empirical evidence supporting the development of adaptive, culturally responsive, and student-centered learning models for elementary education.